Where Have All the Profits Gone? : European Bank Profitability Over the Financial Cycle - Detragiache, Enrica (IMF Working Papers; Working Paper ;, 2018)
The paper investigates EU banks' profitability through the recent financial cycle using banklevel balance sheet and income statement data. We find that banks that were more successful at protecting their profits had a less pronounced deterioration in loan quality and a larger improvement in cost efficiency. They also downsized their assets more aggressively during the crisis, and reduced reliance on wholesale funding more markedly post-crisis. Net interest margins remained broadly stable over the financial cycle, including post-crisis, and there is no clear evidence that aspects of bank business model, such as higher reliance on fees and commission income, were associated with better profitability post-crisis.